Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Personel (Studi Kasus Pada KRI XYZ) - sulistiono, andi; riyanto, Budi; Wahyuni, Sri (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
The research was implemented by author to examine the relation of competence and work motivation to the personel performance in order to accomplish work daily. The analysis will use approaches quantitative method in which some data will be collected from field research and some theories. Field research will take place in a warship xyz. The author will arrange analysis which is used regrresion analysis to examine the correlation personel competence and work motivation to the personel performance by partially and simultaneously. The correlation from competence to personel performance is 0,52, it means competence has correlation and influence to the personel performance. The result of correlation analysis from work motivation to personel performance is 0,615, it has meaning that work motivation has strong correlation and give influence to the personel performance. Regression linear analysis showed the value of t table from work motivation bigger than t table of competence to the personel performance, it means that work motivation has influence stronger than competence to the personel performance.